2011
DOI: 10.1016/j.bpc.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of internal structured repeats increases the stability of a leucine-rich repeat protein, YopM

Abstract: Mapping the stability distributions of proteins in their native folded states provides a critical link between structure, thermodynamics, and function. Linear repeat proteins have proven more amenable to this kind of mapping than globular proteins. C-terminal deletion studies of YopM, a large, linear leucine-rich repeat (LRR) protein, show that stability is distributed quite heterogeneously, yet a high level of cooperativity is maintained [1]. Key components of this distribution are three interfaces that stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…In contrast, HX studies observe unfolding reactions in the context of the folded state, such that structural modules (foldons) (47) can stabilize one another. Work on consensus α-helical repeat proteins (48,49) and on deletion studies of LRR proteins (25,50) have shown that the interfacial interactions between repeats are strongly stabilizing. Thus, we expect the highly stable C terminus of PP32 to protect neighboring repeats from exchange, broadening the observed stability map toward the N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HX studies observe unfolding reactions in the context of the folded state, such that structural modules (foldons) (47) can stabilize one another. Work on consensus α-helical repeat proteins (48,49) and on deletion studies of LRR proteins (25,50) have shown that the interfacial interactions between repeats are strongly stabilizing. Thus, we expect the highly stable C terminus of PP32 to protect neighboring repeats from exchange, broadening the observed stability map toward the N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…27, 28, 29, 30 YopM has a nuclear localization signal in its C-terminus, and is translocated into the nucleus via an endocytic pathway. 31, 32, 33 The first identified targets of YopM were ribosomal S6 protein kinase 1 (RSK1) and protein kinase C-like 2 (PRK2).…”
mentioning
confidence: 99%
“…Moreover, recent work from several groups suggests that, even though large proteins can generally be broken down into smaller units by domain dissection, the folding of these component domains may not be independent, and thus what is seen for free-standing small-domain proteins may not be applicable to the universe of larger proteins in the proteomes of all organisms. Specifically, the domains of repeat proteins have been found to display context-dependent folding [15,16]. In addition, the coupling of domains of large proteins is often a key part of the function of the large protein [17].…”
Section: Recent In-vitro Protein Folding Research Advances With Potenmentioning
confidence: 99%